“Die regverdige sal uit die geloof lewe.” Oor die kritiese funksie van die leer van die regverdiging van die goddelose - Theron, PF (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
This commemorative lecture deals with the fundamental doctrine of the Reformation that was of prime importance in the oeuvre of Willie Jonker i. e. the doctrine of justification. The article highlights the criteriolocal (respectively: ecumenical) character of this doctrine. In the process special attention is paid to the Greek expression pistis Christou. The pivotal role of this doctrine with regard to the unity of the church, which occupied Jonker’s thinking for many decades, is indicated.